Matematică
ecaterina123
2015-11-13 02:27:15
sa se calculeze z+1z pt z= (--1+i radical3) 2
Răspunsuri la întrebare
ade15
2015-11-13 03:42:12

z= (--1+i radical3) 2 este solutie a ecuatiei z²+z+1=0 z+1z =(z²+1)/z=-z/z=-1

XxDX
2015-11-13 03:43:27

[latex]it z = dfrac{-1+isqrt3}{2} \;\ \;\ dfrac{1}{z} = dfrac{2}{-1+isqrt3} = dfrac{2(-1-isqrt3)}{(-1)^2-(isqrt3)^2} =dfrac{2(-1-isqrt3)}{1 +3} = \;\ \;\ =dfrac{2(-1-isqrt3)}{4} = dfrac{-1-isqrt3}{2} [/latex] [latex]it z+dfrac{1}{z} = dfrac{-1+isqrt3}{2} + dfrac{-1-isqrt3}{2} = dfrac{-1+isqrt3-1-isqrt3}{2} = \;\ \;\ = dfrac{-2}{2}=-1.[/latex]

Adăugați un răspuns